Method for producing granule, and granule
Patent Information
- Application Number
- JP2024209656
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-12-27
- Filing Date
- 2024-12-02
- Publication Date
- 2025-02-26
- Estimated Expiration
- 2040-11-05
AI Technical Summary
【0011】 本発明の一側面によれば、機能材料が保持された流動性に優れる顆粒の製造方法を提供することができる。
Smart Images

Figure 2025027113000015 
Figure 2025027113000016 
Figure 2025027113000017
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing granules and to the granules. [Background technology]
[0002] Enzymes, yeasts, flavorings, etc. are functional materials with low stability that are easily affected by environmental changes such as heat and acid. When using such ingredients for food or pharmaceutical applications, it is important to maintain stability by assuming environmental changes such as temperature and humidity. For example, Patent Document 1 describes a method for obtaining a dry and stabilized composition of bioactive materials by mixing bioactive materials such as proteins and enzymes with other ingredients in an aqueous solvent to form a sticky slurry, flash-freezing the slurry in liquid nitrogen, and further drying it under vacuum. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2015-517985 A Summary of the Invention [Problem to be solved by the invention]
[0004] The dry composition described in Patent Document 1 may be used in the form of a powder or granule. When using powdered materials in food and pharmaceutical products, excellent fluidity is required to prevent lumping and line clogging.
[0005] An object of one aspect of the present invention is to provide a method for producing granules that retain a functional material and have excellent flowability. [Means for solving the problem]
[0006] The inventors discovered that by using a suspension of crystalline sugar and / or sugar alcohol in which some of the sugar alcohol is in a crystalline state and spray-drying this together with a functional material under low-temperature conditions, granules containing the functional material have excellent fluidity, and thus completed the present invention.
[0007] In one aspect, the present invention provides a method for producing granules, comprising the steps of obtaining a mixed suspension containing at least one selected from the group consisting of crystalline sugars and crystalline sugar alcohols and a functional material, the sugar and / or sugar alcohol being partially contained in a crystalline state, and spray-drying the mixed suspension at a low temperature. Preferably, the spray-drying is carried out under conditions of an inlet air temperature of 0 to 60°C.
[0008] Another aspect of the present invention provides granules containing at least one selected from the group consisting of crystalline sugars and crystalline sugar alcohols, and a functional material, wherein a portion of the sugar and / or sugar alcohol is in a crystalline state and another portion is in a non-crystalline state.
[0009] In the granules, the amorphous sugar and / or sugar alcohol and the functional material are preferably retained in gaps formed between the crystalline sugar and / or sugar alcohol.
[0010] In the above granules or the manufacturing method thereof, the sugar and sugar alcohol are preferably monosaccharides, disaccharides, trisaccharides and their sugar alcohols. The average particle size of the sugar and / or sugar alcohol in a crystalline state may be 1 to 80 μm. The functional material may be an enzyme, a microorganism or a flavoring. Effect of the Invention
[0011] According to one aspect of the present invention, there is provided a method for producing granules having excellent flowability and retaining a functional material. [Brief description of the drawings]
[0012] [Figure 1] 1 shows the results of observation of sugar suspension A and sugar suspension B using a digital microscope. [Diagram 2]1 shows the results of observation of granular particles according to Examples 1 to 3 using a scanning electron microscope (SEM). [Diagram 3] 1 shows the results of observation of sugar suspension D using a digital microscope. [Figure 4] 4 shows the results of observation of granular particles according to Example 4 using a scanning electron microscope (SEM). [Diagram 5] 1 shows the results of observation of granular particles according to Example 5 and Comparative Examples 1 and 2 using a scanning electron microscope (SEM). [Figure 6] 1 shows the results of observation of granular particles according to Example 6 and Comparative Example 3 using a scanning electron microscope (SEM). [Figure 7] 1 shows the results of observation of granular particles according to Example 7 using a scanning electron microscope (SEM). [Figure 8] 1 shows the results of observation of granular particles according to Example 8 using a scanning electron microscope (SEM). [Figure 9] 1 shows the results of observation of granular particles according to Example 9 using a scanning electron microscope (SEM). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] Hereinafter, embodiments of the present invention will be described in detail, however, the present invention is not limited to the following embodiments.
[0014] <Granule manufacturing method> One embodiment of the present invention is a method for producing granules, comprising a step of obtaining a mixed suspension containing at least one selected from the group consisting of crystalline sugars and crystalline sugar alcohols and a functional material, in which a portion of the sugar and / or sugar alcohol is contained in a crystalline state (mixing step), and a step of spray-drying the mixed suspension under low-temperature conditions (spray-drying step).
[0015] First, the mixing step will be described. In one embodiment, the mixing step includes a step of crystallizing a solution containing at least one selected from the group consisting of crystalline sugar and crystalline sugar alcohol (crystallization step) and a step of adding a functional material (addition step).
[0016] In the crystallization step, first, a solution (sugar solution) containing crystalline sugar and / or crystalline sugar alcohol is prepared. The solution may contain at least one selected from the group consisting of crystalline sugar and crystalline sugar alcohol, and a solvent. The solvent is, for example, an organic solvent such as ethanol, methanol, acetone, isopropanol, or water.
[0017] From the viewpoint of improving operability in the mixing step, the crystalline sugar and crystalline sugar alcohol are preferably monosaccharides, disaccharides, trisaccharides, and sugar alcohols thereof.
[0018] Examples of monosaccharides include glucose, galactose, mannose, fructose, allose, and allulose. Examples of disaccharides include isomaltulose, sucrose, lactulose, lactose, maltose, trehalose, and cellobiose. Examples of trisaccharides include nigerotriose, maltotriose, and raffinose. Isomaltulose is a disaccharide that is a registered trademark of Mitsui Sugar Co., Ltd. under the name "palatinose."
[0019] Examples of sugar alcohols include sorbitol, erythritol, xylitol, maltitol, lactitol, mannitol, α-glucopyranosyl-1,1-mannitol, and α-glucopyranosyl-1,6-sorbitol.
[0020] The above-mentioned crystalline sugars and sugar alcohols may be used alone or in combination of two or more.
[0021] The content of sugar and / or sugar alcohol in the sugar solution is not particularly limited as long as it is a concentration at which crystals are formed in the crystallization step described below. The content of crystalline sugar and / or sugar alcohol contained in the sugar solution is preferably 40% by mass or more, more preferably 45% by mass or more, and even more preferably 50% by mass or more, based on the total amount of the sugar solution, from the viewpoint of efficient crystallization in the crystallization step. The content of crystalline sugar and / or sugar alcohol is preferably 90% by mass or less, more preferably 80% by mass or less, and even more preferably 70% by mass or less, based on the total amount of the sugar solution, from the viewpoint of maintaining good operability in the mixing step and the spray drying step. The content of sugar and / or sugar alcohol may be a content that is a concentration equal to or higher than the saturated solubility. In other words, the sugar solution may be a supersaturated solution.
[0022] The Brix value (Bx) of the sugar solution is preferably 50 or more, more preferably 55 or more, and even more preferably 65 or more, from the viewpoint of efficient crystallization in the crystallization step, and is preferably 85 or less, more preferably 80 or less, and even more preferably 75 or less, from the viewpoint of maintaining good operability in the mixing step and the spray drying step. In this specification, the Brix value (Bx) means the RefBrix value calculated from the refractive index of the sugar solution, and can be measured with a Brix meter (for example, a digital refractometer (RX-5000), manufactured by Atago Co., Ltd.).
[0023] When preparing a sugar solution, the solvent may be heated, and then the crystalline sugar and / or sugar alcohol may be added and dissolved. In this case, the temperature of the solvent is not particularly limited, but is, for example, 70° C. or higher. The temperature of the solvent may be 100° C. or lower.
[0024] The sugar liquid may contain components other than crystalline sugar and / or sugar alcohol. For example, the sugar liquid may contain non-crystalline sugar and non-crystalline sugar alcohol. Preferably, the sugar liquid contains only crystalline sugar and / or sugar alcohol.
[0025] In the crystallization step, for example, a portion of the crystalline sugar and / or sugar alcohol may be crystallized by cooling the sugar liquid (cooling crystallization method), or crystallization may be performed by reactive crystallization method. This makes it possible to obtain a suspension (sugar suspension) containing crystalline sugar and / or sugar alcohol and amorphous sugar and / or sugar alcohol. In the present invention, "crystalline sugar and / or sugar alcohol" refers to solid sugar and / or sugar alcohol whose constituent atoms are three-dimensionally regularly repeated, and "amorphous sugar and / or sugar alcohol" refers to solid or liquid sugar and / or sugar alcohol that does not have such a regularly repeated structure.
[0026] When crystallization is carried out by cooling crystallization, the temperature of the sugar solution upon cooling (cooling temperature) may be set depending on the type of crystalline sugar and / or sugar alcohol, and is, for example, 60° C. or lower, 50° C. or lower, or 45° C. or lower. The cooling temperature may be 5° C. or higher, 10° C. or higher, 15° C. or higher, or 20° C. or higher.
[0027] In the crystallization step, a means for controlling the growth of crystals may be carried out to adjust the average particle size of the crystals. The means may be carried out by the so-called build-up method, and may be, for example, a method of performing crystallization while performing ultrasonic irradiation. That is, the crystallization step may further include a step of performing ultrasonic irradiation (ultrasonic irradiation step). Ultrasonic irradiation can be carried out, for example, by using an ultrasonic irradiation device (e.g., ULTRA SONIC HOMOGENIZER UH-500 manufactured by SMT Co., Ltd.) on the sugar suspension obtained in the above-mentioned operation of crystallization by cooling the sugar liquid. The ultrasonic irradiation conditions (frequency of ultrasonic irradiation, temperature of the sugar suspension, ultrasonic irradiation time) may be appropriately adjusted according to the average particle size of the desired crystals. When the ultrasonic irradiation step is carried out, the liquid after ultrasonic irradiation can be used as the sugar suspension.
[0028] The crystallization rate in the crystallization step is preferably 10% by mass or more, more preferably 20% by mass or more, and even more preferably 30% by mass or more, from the viewpoint of easily obtaining granules with excellent fluidity. The crystallization rate is preferably 80% by mass or less, more preferably 60% by mass or less, and even more preferably 40% by mass or less, from the viewpoint of maintaining good operability in the spray drying step. The crystallization rate in this specification is calculated by placing 1 g of the sugar suspension in a 1.5 ml Eppendorf tube, centrifuging it at 16,000 rpm for 1 minute using a centrifuge (e.g., M150IV manufactured by Sakuma Seisakusho Co., Ltd.), discarding the supernatant, and dividing the remaining amount of crystals by the mass of the sugar suspension.
[0029] The crystallization rate can be adjusted by performing operations to physically or chemically add or remove crystals, such as filter filtration, centrifugation, gravity settling, dissolution by adding water / heating, adjustment of consumption of crystal components accompanying chemical reactions, etc. Alternatively, it can also be adjusted by operations to increase crystals, such as crystallization operations (cooling crystallization, evaporative crystallization, non-solvent crystallization, reactive crystallization, salting out), introduction and mixing of crystal components, etc.
[0030] The sugar suspension may contain crystal nuclei, and the size of the crystal nuclei is not particularly limited as long as the crystal nuclei are large enough to exist stably in the sugar suspension. The size of the crystal nuclei may be, for example, equal to or larger than the critical crystal nucleus.
[0031] The average particle size of the crystalline sugar and / or sugar alcohol obtained by the crystallization step is preferably 1 μm or more, more preferably 5 μm or more, even more preferably 10 μm or more, particularly preferably 20 μm or more, from the viewpoint of maintaining the fluidity of the granules, and is preferably 80 μm or less, more preferably 70 μm or less, even more preferably 60 μm or less, from the viewpoint of preventing the collapse of the granules. That is, the average particle size of the crystalline sugar and sugar alcohol may be 1 to 80 μm, or may be 5 to 80 μm. The average particle size of the crystals can be adjusted by adding or removing a solvent or solute, changing the solvent temperature, dissolving time, or stirring time, crushing with a stirrer or grinder, fractionation by filtration, or crystallization by hydrolysis of the sugar, etc.
[0032] The average particle size in this specification can be measured by a digital microscope. For example, SKM-S31B-PC manufactured by Saito Kogaku Co., Ltd. can be used for the measurement. The major axis of 10 or more crystalline sugars and / or sugar alcohols constituting any 10 or more granules or crystallized particles is measured by the digital microscope, and the average value of the major axes measured is calculated and referred to as the "average particle size."
[0033] The crystallization step may further include a step of shearing the crystals (shearing step) in order to adjust the average particle size of the crystals. The shearing step may be carried out by a so-called breakdown method, in which a physical impact is applied to the crystals contained in the sugar liquid to crush the crystals and adjust the average particle size. In this case, the shearing step may be carried out, for example, after the above-mentioned sugar liquid is crystallized by cooling, using a high-pressure homogenizer (e.g., HV-0A1-1.5S manufactured by Izumi Food Machinery Co., Ltd.) on the obtained sugar suspension. The shearing conditions (temperature of the sugar suspension, load pressure of the homogenizer, and homogenization conditions) may be appropriately adjusted according to the average particle size of the crystals. When the shearing step is carried out, the liquid after shearing can be used as a sugar suspension.
[0034] In one embodiment, the adding step includes adding a functional material to the sugar suspension. The sugar suspension and the functional material are stirred and mixed to obtain a mixed suspension containing crystalline sugar and / or sugar alcohol, amorphous sugar and / or sugar alcohol, and the functional material.
[0035] A functional material is not limited to a material or component that exhibits some function in a composition (e.g., food, medicine, etc.) obtained by combining with other materials. A functional material may be a material that is affected by the surrounding environment such as moisture, heat, light, acid, oxygen, molecular motion, ultraviolet light, electrical interaction, or physical stimuli, or a material that loses its function when heated. More specifically, functional materials include amino acids, peptides (including hormones), proteins (including enzymes and antibodies), fatty acids, vitamins, minerals, microorganisms (e.g., bacteria such as lactic acid bacteria, butyric acid bacteria, natto bacteria, bifidobacteria, and actinomycetes, molds, and yeasts), hormones other than peptides, flavorings, phages, and antibiotics other than peptides.
[0036] The amount of the functional material added may be 0.01 parts by mass or more, 0.05 parts by mass or more, or 0.1 parts by mass or more, and 5 parts by mass or less, 3 parts by mass or less, or 1 part by mass or less, relative to 100 parts by mass of the sugar suspension described above. The amount of the functional material added can be appropriately adjusted depending on the type of functional material.
[0037] In another embodiment, the mixing step described above may be a step of preparing a solution containing crystalline sugar and / or sugar alcohol and a functional material, and then performing the above-mentioned crystallization step to obtain a mixed suspension. In another embodiment, the mixing step may be a step of preparing a mixed suspension containing crystalline sugar and / or sugar alcohol, amorphous sugar and / or sugar alcohol, and a functional material.
[0038] Next, the spray drying process will be described. The spray drying process is a process in which the above-mentioned mixed suspension is spray-dried under low temperature conditions.
[0039] In one embodiment, the spray drying can be performed using a spray dryer. As the spray dryer, for example, OC-16 manufactured by Okawara Kakoki Co., Ltd. can be used.
[0040] The low-temperature condition means a temperature condition (for example, 60°C or lower) lower than the temperature (for example, higher than 60°C) used in conventional spray drying. The low-temperature condition may be a temperature condition at which the function of the functional material is not lost. When spray drying is performed using a sugar solution as the spray liquid, it is necessary to perform spray drying at a high temperature as in the conventional temperature conditions in order to obtain granules. However, in this embodiment, a mixed suspension in which a part of the sugar solution is made into a crystalline state and a functional material is added thereto is used as the spray liquid, so that suitable granules can be obtained even if spray drying is performed at a lower temperature than in the conventional case. As a result, for example, when the functional material is an enzyme, deactivation of the enzyme due to spray drying at a high temperature is suppressed. Also, when the functional material is a flavoring, volatilization of the flavoring due to spray drying at a high temperature is suppressed. The fact that spray drying is performed at a low temperature means that the inlet air temperature (inlet temperature) in the spray dryer is performed at the temperature conditions described above.
[0041] In one embodiment, the inlet air temperature in the spray drying step is preferably 60° C. or less, 55° C. or less, 50° C. or less, 40° C. or less, 35° C. or less, 30° C. or less, 25° C. or less, 20° C. or less, or 15° C. or less. The inlet air temperature may be, for example, 0° C. or more, 5° C. or more, or 10° C. or more. That is, the inlet air temperature in the spray drying step may be 0 to 60° C., or 0 to 50° C.
[0042] The outlet air temperature (exhaust air temperature) in the spray dryer may be, for example, 50°C or less, 40°C or less, 35°C or less, 30°C or less, 25°C or less, 20°C or less, or 15°C or less, or may be 0°C or more, 5°C or more, or 10°C or more.
[0043] The liquid temperature of the mixed suspension in the spray drying step may be, for example, 60°C or lower, 50°C or lower, or 45°C or lower, and may be 10°C or higher, 15°C or higher, or 20°C or higher.
[0044] In the spray drying, other conditions such as the supply amount of the mixed suspension, the atmospheric temperature, and the atmospheric humidity may be appropriately adjusted.
[0045] For example, the atomizer rotation speed in spray drying may be 3000 rpm or more, 5000 rpm or more, or 10000 rpm or more, and may be 25000 rpm or less, 20000 rpm or less, or 18000 rpm or less.
[0046] The spray drying process may further include a post-drying process for the purpose of, for example, adjusting the moisture content of the granules. The post-drying process may, for example, involve blowing air for a predetermined period of time against the granules adhering to the can wall of the spray dryer to further volatilize the moisture in the granules. Alternatively, the granules obtained by spray drying may be stored for a predetermined period of time in a desiccator containing silica gel.
[0047] <Granules> One embodiment of the present invention is a granule containing at least one selected from the group consisting of crystalline sugar and crystalline sugar alcohol, and a functional material, and the crystalline sugar and / or sugar alcohol is partially in a crystalline state and the other portion in an amorphous state. The detailed aspects of the crystalline sugar, crystalline sugar alcohol, and functional material are the same as those described above, and therefore will not be described here. Note that the "granule" in the present invention is an aggregate of particles, and the particles (granule particles) constituting the granule contain at least one selected from the group consisting of crystalline sugar and sugar alcohol, and the functional material.
[0048] The granules according to one embodiment are composed of granule particles in which a portion of the crystalline sugar and / or sugar alcohol is in a crystalline state and the crystalline sugar and / or sugar alcohol aggregate together. In this case, it is preferable that the other portion (other portion) of the crystalline sugar and / or sugar alcohol is in a non-crystalline state and is held in the gaps formed by the aggregated crystalline sugar and / or sugar alcohol. It is also preferable that the functional material is held in the gaps formed by the crystalline sugar and / or sugar alcohol.
[0049] The aggregation of crystalline sugar and / or sugar alcohol can be confirmed by observing the appearance of the granule particles or the morphology of the fracture surface of the granule particles using a scanning electron microscope (SEM) or a digital microscope. In addition, the retention of amorphous sugar and / or sugar alcohol and functional material in the gaps can be confirmed by the following method. (1) The morphology of the granules is observed during heating using a differential scanning calorimeter (DSC, for example, Hitachi High-Tech Science Corporation's Real View DSC (TA7000)). This allows visual confirmation that amorphous sugars and sugar alcohols undergo glass transition as the temperature increases. (2) Using a polarizing microscope (for example, a polarizing microscope (MT9200L) manufactured by Meiji Techno Co., Ltd.), the difference in polarization between the crystalline state and the amorphous state is visually observed.
[0050] The number of crystalline sugars and / or sugar alcohols contained in the granule particles (the number of crystals) is, for example, 10 or more, and may be 50 or more, or 100 or more. The number of crystals may be 1000 or less. The number of crystals can be determined visually by observing with a scanning electron microscope.
[0051] The median diameter of the granule particles is preferably 30 μm or more, more preferably 50 μm or more, and even more preferably 100 μm or more from the viewpoint of maintaining the fluidity of the granules, and is preferably 500 μm or less, more preferably 400 μm or less, and even more preferably 200 μm or less from the viewpoint of preventing the collapse of the granules. The median diameter of the granule particles can be measured by a laser diffraction particle size distribution measuring device (e.g., SALD-2000J manufactured by Shimadzu Corporation).
[0052] The shape of the granule particles may be substantially spherical from the viewpoint of achieving better flowability. The surface of the granule particles may have irregularities from the viewpoint of achieving better flowability.
[0053] The granules according to this embodiment can be obtained, for example, by the above-mentioned production method.
[0054] The granules according to the above-mentioned embodiment have excellent fluidity. Therefore, the granules have excellent operability. Although the reason for this is unclear, the inventors believe that one of the reasons is that the granule particles of this embodiment contain sugar and / or sugar alcohol in a crystalline state, which causes unevenness to form on the surface of the granule particles, thereby reducing the contact surface between the granule particles. It is also believed that the reason is that the sugar and / or sugar alcohol in a crystalline state is more stable than the sugar and / or sugar alcohol in a non-crystalline state, and has low hygroscopicity and adhesiveness, so that adhesion between the granule particles is suppressed. Furthermore, since the granules of this embodiment are obtained by spray drying under low temperature conditions, the sugar and / or sugar alcohol is likely to remain in a crystalline state, and as a result, the granules have excellent fluidity even after spray drying.
[0055] Furthermore, since the granules of the above-mentioned embodiment contain crystalline sugar and / or sugar alcohol, the granule particles are less likely to deteriorate or be damaged by physical or mechanical stimuli, and the particle structure is also highly stable and has excellent storage properties.
[0056] Moreover, the granule according to the embodiment described above has gaps. That is, gaps are formed in the particles constituting the granule. The gaps allow the solvent to easily penetrate into the granule, so the granule of the present invention is excellent in immediate solubility and immediate disintegration.
[0057] In addition, since the granules are obtained by spray drying under low temperature conditions, the functions of the functional materials contained therein are not easily lost due to heat. In other words, the granules retain the functions of the functional materials well even after the drying process. Usually, when obtaining granules by spray drying, it is difficult to obtain suitable granules unless the spray drying is performed under higher temperature conditions. However, since the granules according to the present embodiment use a mixed suspension containing crystalline sugar and / or sugar alcohol as the spray liquid for spray drying, suitable granules can be easily obtained even under low temperature conditions.
[0058] In addition, the method for producing granules according to the above-mentioned embodiment can omit the step of drying by vacuum freezing or the step of heating the mixed suspension before spray drying, making it possible to produce granules containing functional materials in a simpler manner than conventional methods.
[0059] The granules according to the above-described embodiments can be used as materials to be added to, for example, foods, food additives, pharmaceuticals, cosmetics, quasi-drugs or pharmaceuticals, animal feed, fertilizers, fragrances, antibiotics, soil conditioners, etc. EXAMPLES
[0060] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples.
[0061] <Example 1> Isomaltulose enzyme reaction solution (manufactured by Mitsui Sugar Co., Ltd.) was added to water and dissolved while heating to 80°C in a hot water bath, to obtain 5 kg of isomaltulose solution (sugar solution) with a total solution content of 65% by mass. 5 kg of this isomaltulose solution was placed in a metal container, and the sugar solution was rapidly cooled to 30°C, and then treated with a high-pressure homogenizer (manufactured by Izumi Food Machinery Co., Ltd., "HV-0A1-1.5S") at 20 MPa and 60 Hz for 2 hours. When the solution after the treatment (also called sugar suspension A) was observed with a digital microscope (manufactured by Saito Kogaku Co., Ltd., "SKM-S31B-PC", magnification: 500 times), isomaltulose crystals with a particle size of 20 to 80 μm were contained in the sugar suspension A. The results of the observation of sugar suspension A with a digital microscope are shown in Figure 1 (a). The crystallization rate of sugar suspension A was 40%.
[0062] A mixed suspension (also called mixed suspension A) was obtained by adding alcohol dehydrogenase (ADH) (manufactured by Oriental Yeast Co., Ltd., "yeast-derived alcohol dehydrogenase", yeast-derived, molecular weight: 141-151 kDa) and bovine serum albumin (BSA) (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., "bovine serum albumin") in an amount of 0.1% by mass based on the total solid content to sugar suspension A. At this time, the mass ratio of ADH to BSA was ADH:BSA=1:2.
[0063] <Example 2> Isomaltulose (manufactured by Mitsui Sugar Co., Ltd.) was added to water and dissolved while heating to 80°C in a hot water bath to obtain 5 kg of an isomaltulose solution (sugar solution) containing 57.5% by mass based on the total amount of the solution. 5 kg of this isomaltulose solution was placed in a metal container and rapidly cooled until the sugar solution reached 30°C. While maintaining the temperature at 35°C or less, the solution was treated under the same conditions as in Example 1 using a high-pressure homogenizer. When the solution after the treatment (also called sugar suspension B) was observed with a digital microscope (magnification: 500 times), it was found that isomaltulose crystals of 20 to 80 μm were contained in the sugar suspension B. The results of the observation of sugar suspension B with a digital microscope are shown in FIG. 1(b). The crystallization rate of sugar suspension B was 40%.
[0064] Trehalose (manufactured by Hayashibara Corporation, "crystalline trehalose") was added and dissolved in sugar suspension B in an amount equivalent to 5% by mass based on the total solid content and trehalose content of sugar suspension B. Furthermore, ADH and BSA were added in the same amounts as in Example 1 to obtain a mixed suspension (also referred to as mixed suspension B).
[0065] <Example 3> A mixed suspension (also referred to as mixed suspension C) was obtained in the same manner as in Example 2, except that the amount of trehalose added was changed to 10 mass %.
[0066] [Spray drying] The mixed suspensions A, B, and C were each spray-dried using a spray dryer (manufactured by Okawara Kakoki Co., Ltd., "OC-16") under the conditions shown in Table 1. After 60 minutes of spraying, the granules adhering to one half of the spray dryer can wall were collected. Then, for mixed suspensions B and C, air was blown for an additional 30 to 40 minutes, and the granules adhering to the other half of the spray dryer can wall were collected. Hereinafter, the granules collected immediately after 60 minutes of spraying are referred to as "primary dried granules," and the granules collected after air blowing are referred to as "secondary dried granules."
[0067] [Table 1]
[0068] [Appearance Observation] The appearance of the granule particles was observed by scanning electron microscope (SEM) for the primary dried granules prepared from each mixed suspension. The observation results are shown in Figure 2. Figure 2(a) is an SEM image (magnification: 250x) of the primary dried granules obtained from mixed suspension A, Figure 2(b) is an SEM image (magnification: 250x) of the primary dried granules obtained from mixed suspension B, and Figure 2(c) is an SEM image (magnification: 250x) of the primary dried granules obtained from mixed suspension C. As shown in each image, it can be seen that the obtained granules are formed by aggregation of crystalline sugar (isomaltulose). In addition, when the appearance and cross-section of the granule particles were observed, atypical solid phases (lumps) of amorphous sugar and functional materials were observed in the gaps formed by the crystalline sugars.
[0069] [Moisture content of granules] The free water content of each granule was measured using a near-infrared moisture meter (Kett Electric Laboratory, "NIR moisture meter KJT-230"). The total moisture content of each granule was measured by the following method. Approximately 5 g of granules were weighed using an electronic balance (METTLER TOLEDO, "ME204"), and distilled water was added until the total weight was approximately 25 g, and the weight at that point was measured. After the granules were completely dissolved, the total solid content in the granule solution was calculated from the refractive index measured using a Refbrix meter (ATAGO Co., Ltd., "RX-5000α"). The difference between the initially measured granule weight and the weight of the total solid content in the granule solution was calculated as the total moisture content in the granules. The results are shown in Table 2.
[0070] [Table 2]
[0071] [Liquidity assessment] The flowability of the primary dried granules according to each Example was evaluated by visual and manual inspection. The evaluation criteria were as follows. As a result, the flowability of all the granules according to Examples 1 to 3 was evaluated as ◯. 〇: Smooth △: It is smooth but hardens when pressed. ×: Sticky or lumpy
[0072] Furthermore, for the primary dried granules according to each Example, the "flowability index" and "flowability index" proposed by RL Carr were calculated (Carr, RL "Evaluating flow properties of solids." Chem. Eng. (1965) 72 (163-168)). For the primary dried granules of each Example, the angle of repose (°) and spatula angle (°) of the granules were determined using a multi-function powder property measuring instrument (manufactured by Seishin Enterprise Co., Ltd., "Multitester MT-02"). For the primary dried granules of Example 3, the compressibility (%) and uniformity (-) were further determined, and an index corresponding to each measured value was obtained based on Carr's theory. The indexes of each measured value were added up to obtain a flowability index, and the flowability was evaluated based on Carr's evaluation criteria listed in Table 3. The above results are shown in Table 4.
[0073] In addition, the collapse angle (°) and difference angle (°) of the primary dried granules according to each Example were determined using the above device. For the primary dried granules of Example 3, the degree of dispersion (%) was further determined, and the indices corresponding to the measured values obtained based on Carr's theory and the index based on the fluidity index were added together to obtain a flowability index. Based on Carr's evaluation criteria shown in Table 3, the flowability of the primary dried granules according to Example 3 was evaluated. The results are shown in Table 4.
[0074] [Table 3]
[0075] [Table 4]
[0076] [Evaluation of enzyme activity (1)] In carrying out the spray drying, the extent to which the ADH contained in the mixed suspension was inactivated over time was confirmed. The mixed suspension was sampled and diluted with distilled water so that the ADH concentration was 0.25 U / mL. After dilution, the mixture was reacted with the ADH substrate in an atmosphere of 25°C, and the absorbance at 340 nm of the reaction solution was measured using a spectrophotometer (Shimadzu Corporation, "UVmini-1240"). The absorbance of the ADH reagent adjusted to 0.25 U / mL was set as 100%, and the ratio of the absorbance at each elapsed time was taken as the activity retention rate. The change in activity retention rate in each mixed suspension is shown in Table 5.
[0077] [Table 5]
[0078] From Table 5, it was confirmed that the enzyme activity was sufficiently maintained during the spray drying of the mixed suspensions prepared by the methods according to Examples 1 to 3.
[0079] [Evaluation of enzyme activity (2)] The ADH activity retention rate was measured in the same manner as in [Evaluation of enzyme activity (1)] for the granules obtained in Examples 1 to 3. The results are shown in Table 6.
[0080] [Table 6]
[0081] [Evaluation of enzyme activity (3)] The change in enzyme activity during low-temperature storage was confirmed for the primary dried granules of Example 1, and the primary and secondary dried granules of Example 2. Each granule was placed in an aluminum bag with a zipper (Lamizip AL-J, manufactured by Seizo Nippon Co., Ltd.) and stored for a specified number of days in an environment at -20°C and an environment at 4°C, and the change in activity retention rate of each granule during the low-temperature storage period was measured using the same method as described above. The results are shown in Table 7.
[0082] [Table 7]
[0083] <Example 4> Trehalose ("Crystalline Trehalose" manufactured by Hayashibara Co., Ltd.) was added to water and dissolved while heating to 80°C in a hot water bath to obtain 5 kg of trehalose solution (sugar solution) with a Brix value (Bx) of 62. 5 kg of this trehalose solution was placed in a metal container and rapidly cooled to 30°C. While maintaining the temperature at 30°C or less, the solution was treated for 15 minutes at POWER MONITOR level 5 using an ultrasonic oscillator ("ULTRA SONIC HOMOGENIZER UH-500" manufactured by SMT Co., Ltd.). When the solution after the treatment (also called sugar suspension D) was observed with a digital microscope (magnification: 500 times), trehalose crystals of 20 to 80 μm were contained in sugar suspension D. The results of the digital microscope observation of sugar suspension D are shown in FIG. 3.
[0084] To 4 kg of sugar suspension D, 260 g of an aqueous sucrose solution having a Bx of 50 was added. Furthermore, ADH and BSA were added in the same amounts as in Example 1 to obtain a mixed suspension (also referred to as mixed suspension D).
[0085] [Spray drying] The mixed suspension D was spray-dried using a spray dryer under the conditions shown below. After 60 minutes of spraying, the granules attached to one half of the spray dryer can wall (primary dried granules) were collected. After that, air was blown for another 30 to 40 minutes, and the granules attached to the other half of the spray dryer can wall (secondary dried granules) were collected. <Spray drying conditions> Ambient temperature: 28.4~28.6℃ Ambient humidity: 33~35% Inlet air temperature: 30.2℃ Outlet air temperature: 26.1~28.6℃ Supply amount: 40~45mL / min Adomizer speed: 15118~17081rpm Airflow rate: 60Hz Exhaust air volume: 37Hz
[0086] [Appearance Observation] The appearance of the granule particles of the primary dried granules of Example 4 was observed by a scanning electron microscope (SEM) (magnification: 1000 times). The observation results are shown in Figure 4. As shown in Figure 4, it can be seen that the obtained primary dried granules are formed by aggregation of crystalline sugar (trehalose). Furthermore, when the appearance and cross section of the granule particles were observed, an atypical solid phase (lump) of amorphous sugar and functional material was observed in the gaps formed by the crystalline sugar.
[0087] [Liquidity assessment] The flowability of the primary dried granules according to Example 4 was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the flowability was evaluated as ◯.
[0088] Furthermore, the angle of repose (°) and spatula angle (°), which are indices of fluidity, and the angle of collapse (°) and angle of difference (°), which are indices of spoutability, were determined for the primary dried granules of Example 4 by the same method as described above. As a result, the angle of repose was 32.5°, the spatula angle was 34.1°, the angle of collapse was 20.5°, and the angle of difference was 12.0°.
[0089] [Water activity adjustment] Granules with different water activities were prepared from the granules according to Example 4. Granules (granule X) were prepared by wrapping the secondary dried granules according to Example 4 in aluminum foil, and granules (granule Y) were prepared by drying the primary dried granules according to Example 4 under reduced pressure for 20 minutes at room temperature (24-27°C) and then placing them in a desiccator with a humidity control of 20-30% RH using silica gel. The water activities of granules X and Y were measured using a water activity measuring device (METER, "Dew Point water activity Meter AquaLAb Series4TE"). As a result, the water activity (Aw) of granule X before the storage test shown below was 0.7561, and the water activity (Aw) of granule Y was 0.4141.
[0090] Granule X wrapped in aluminum foil and Granule Y stored in a desiccator were each divided into two groups, one stored at room temperature (24-27°C) and the other stored in a refrigerator (4-8°C). In other words, for each of Granule X and Granule Y, a group stored at room temperature and a group stored in a refrigerator were set up.
[0091] [Evaluation of enzyme activity (4)] The absorbance at 340 nm of Granules X and Y after storage at room temperature or in a refrigerator was measured using the same method as in the above-mentioned "Evaluation of Enzyme Activity (2)". Meanwhile, Mixed Suspension D was diluted with distilled water so that the ADH concentration became 0.25 U / mL. After dilution, it was reacted with the ADH substrate in an atmosphere of 25°C, and the absorbance at 340 nm of the reaction solution was measured using a spectrophotometer. The absorbance measured from Mixed Suspension D was taken as 100%, and the absorbance measured from each granule was taken as the activity retention rate. The change in activity retention rate with storage time is shown in Table 8.
[0092] [Table 8]
[0093] <Example 5, Comparative Examples 1 and 2> Sugar (trehalose) was added to warm water and dissolved while heating to 90°C in a hot water bath, obtaining a sugar solution with a Brix value of 62. This 90°C sugar solution was placed in a metal container and rapidly cooled to 30°C to obtain 4 kg of a sugar suspension (also called sugar suspension E). Meanwhile, an enzyme solution containing 0.248 g of lactate dehydrogenase (LDH) (manufactured by Oriental Yeast Co., Ltd.), 0.322 g of BSA, 130 g of phosphate buffered saline (pH 7.5), and 130 g of trehalose was prepared. This enzyme solution was added to sugar suspension E immediately after the liquid temperature reached 30°C, obtaining a mixed suspension (also called mixed suspension E). The BSA, phosphate buffered saline, and trehalose in the enzyme solution were added as general protective ingredients.
[0094] The mixed suspension E was spray-dried using the above-mentioned spray dryer. Granules according to Example 5 were obtained by spray-drying under conditions of an inlet air temperature of 30.0°C and an outlet air temperature of 23.5°C. Meanwhile, granules according to Comparative Example 1 were obtained by spray-drying under conditions of an inlet air temperature of 100.0°C and an outlet air temperature of 76.7°C, and granules according to Comparative Example 2 were obtained by spray-drying under conditions of an inlet air temperature of 165.0°C and an outlet air temperature of 121.4°C. The spray-drying conditions other than the temperature were unified as follows in all the Examples and Comparative Examples. Airflow rate: 60.0Hz Exhaust air volume: 37.0Hz Static pressure inside the tower: Slightly positive pressure Atomizer rotation speed: 18000 rpm Equipment shape: Wet type Supply amount: 42~45mL / min Mixed suspension temperature: 26.9~28.0℃
[0095] [Appearance Observation] The appearance of the particles of the granules according to Example 5 and Comparative Examples 1 and 2 was observed using a scanning electron microscope (SEM). The observation results (magnifications: 500 and 1000 times) are shown in Fig. 5. Fig. 5(a) shows the observation results of the granules (granule particles) according to Example 5, Fig. 5(b) shows the observation results of the granules according to Comparative Example 1, and Fig. 5(c) shows the observation results of the granules according to Comparative Example 2. As shown in Fig. 5(a), it can be seen that the granules according to Example 5 are formed by agglomeration of crystalline sugar.
[0096] [Liquidity assessment] The fluidity of the granules of Example 5 and Comparative Examples 1 and 2 was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity of the granules of Example 5 was evaluated as ◯, while the fluidity of the granules of Comparative Examples 1 and 2 was evaluated as ×.
[0097] Furthermore, the angle of repose (°) and spatula angle (°), which are indicators of fluidity, were determined for the granules of Example 5 and Comparative Example 2 by the same method as described above. The results are shown in Table 9.
[0098] [Table 9]
[0099] [Evaluation of enzyme activity] The granules of Example 5 and Comparative Example 2 were used to confirm the extent to which the LDH activity in the granules was maintained over time. Granules stored at room temperature (25°C) for a specified number of days were collected and diluted with distilled water to an LDH concentration of 0.25U / mL. After dilution, the granules were reacted with an LDH substrate in an atmosphere of 25°C, and the absorbance at 340 nm of the reaction solution was measured using a spectrophotometer (Shimadzu Corporation, "UVmini-1240"). The absorbance of the LDH reagent adjusted to 0.25U / mL was set as 100%, and the ratio of the absorbance at each elapsed day was taken as the activity retention rate, and the results are shown in Table 10.
[0100] [Table 10]
[0101] <Example 6, Comparative Example 3> A mixed suspension (also referred to as mixed suspension F) was obtained in the same manner as in Example 5 above, except that LDH was changed to ADH.
[0102] The mixed suspension F was spray-dried using the above-mentioned spray dryer. The granules according to Example 6 were obtained by spray-drying under conditions of an inlet air temperature of 30.0°C and an outlet air temperature of 23.5°C. On the other hand, the granules according to Comparative Example 3 were spray-dried under conditions of an inlet air temperature of 100.0°C and an outlet air temperature of 76.7°C. The spray-drying conditions other than the temperature were the same as those in Example 5.
[0103] [Appearance Observation] The appearance of the granules according to Example 6 and Comparative Example 3 was observed using a scanning electron microscope (SEM). The observation results (magnification: 500 times) are shown in Fig. 6. Fig. 6(a) shows the observation results of the granules according to Example 6, and Fig. 6(b) shows the observation results of the granules according to Comparative Example 3. As shown in Fig. 6(a), it can be seen that the granules according to Example 6 are formed by agglomeration of crystalline sugar.
[0104] [Liquidity assessment] The fluidity of the granules of Example 6 and Comparative Example 3 was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity of the granules of Example 6 was evaluated as ◯, while the fluidity of the granules of Comparative Example 3 was evaluated as ×.
[0105] Furthermore, the angle of repose (°) and spatula angle (°), which are indicators of fluidity, were determined for the granules of Example 6 and Comparative Example 3 by the same method as described above. The results are shown in Table 11.
[0106] [Table 11]
[0107] <Example 7> Lactic acid bacteria Lb.paracasei JCM8130 T was purchased from the Riken Bioresource Research Center and cultured to prepare a seed culture. The seed culture was cultured at 37°C for 48 hours using 500mL of MRS liquid medium. The absorbance of the obtained culture solution at 660nm was measured to confirm that the culture solution of lactic acid bacteria was in a stationary state. The supernatant was removed from the MRS medium after the culture, and the precipitate fraction was obtained as a thick pellet of lactic acid bacteria. 130g of trehalose, 26.1g of skim milk, 2.61g of ascorbic acid, and 130g of phosphate buffered saline (pH 7.5) were added as protective agents to the obtained pellet of lactic acid bacteria to prepare a lactic acid bacteria liquid. The lactic acid bacteria liquid was kept under stirring at room temperature of 25°C until it was mixed with the sugar suspension described below. Meanwhile, 4kg of sugar suspension E was prepared by the same method as in Example 5. The lactic acid bacteria liquid was added to the sugar suspension E at 30°C to obtain a mixed suspension (also called mixed suspension G).
[0108] The mixed suspension G was spray-dried using the above-mentioned spray dryer to obtain granules according to Example 7. At this time, the spray-drying conditions were all the same as those in Example 5.
[0109] [Appearance Observation] The appearance of the granule particles of the granules of Example 7 was observed by a scanning electron microscope (SEM). The observation results (magnification: 1000 times) are shown in Figure 7. As shown in Figure 7, it can be seen that the granules of Example 7 are formed by aggregation of crystalline sugar.
[0110] [Liquidity assessment] The fluidity of the granules of Example 7 was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity was evaluated as ◯.
[0111] Furthermore, the angle of repose (°) and spatula angle (°), which are indices of fluidity, and the angle of collapse (°) and angle of difference (°), which are indices of spoutability, were determined for the granules of Example 7 by the same method as described above. As a result, the angle of repose was 32°, the spatula angle was 50.8°, the angle of collapse was 21°, and the angle of difference was 11°.
[0112] [Evaluation of lactic acid bacteria viability] The granules of Example 7 were used to confirm the extent to which the lactic acid bacteria in the granules were maintained over time. The granules were stored for a specified number of days under each environment of 4°C, 25°C, and 37°C, and serially diluted 100-fold five times using 2.5 mM phosphate buffered saline (pH 7.5). 1 mL of each dilution was dropped into a sterilized petri dish, and then 20 mL of BCP-added agar medium kept at 50°C was poured into the petri dish containing the dilution. After culturing for 72 hours in an incubator at 37°C, the number of lactic acid bacteria colonies formed in the petri dish was counted. The number of lactic acid bacteria (CFU / g) contained in 1 g of granules was calculated from the dilution ratio. Table 12 shows the change in the number of lactic acid bacteria (Log(CFU / g)) over the number of days.
[0113] [Table 12]
[0114] <Example 8> A gum arabic solution was prepared by completely dissolving 330 g of gum arabic in 500 g of warm water. The gum arabic solution was adjusted to a liquid temperature of 60°C, and 165 g of medium chain fatty acid oil (MCT, Nisshin MCT Oil, manufactured by Nisshin Oillio Co., Ltd.) was mixed therein, and emulsification treatment was performed using the same ultrasonic oscillator as in Example 4 at POWER MONITOR level 5. The emulsification treatment conditions were 30 seconds of operation and 30 seconds of rest repeated three times. In this way, an MCT emulsion was obtained. Meanwhile, 4 kg of sugar suspension E was prepared by the same method as in Example 5. The MCT emulsion was added to sugar suspension E at 30°C to obtain a mixed suspension (also called mixed suspension H).
[0115] The mixed suspension H was spray-dried using the above-mentioned spray dryer to obtain granules according to Example 8. At this time, the spray-drying conditions were all the same as those in Example 5.
[0116] [Appearance Observation] The appearance of the granule particles of the granules of Example 8 was observed by a scanning electron microscope (SEM). The observation results (magnification: 1000 times) are shown in Figure 8. As shown in Figure 8, it can be seen that the granules of Example 8 are formed by aggregation of crystalline sugar.
[0117] [Liquidity assessment] The fluidity of the granules of Example 8 was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity was evaluated as ◯.
[0118] Furthermore, the angle of repose (°) and spatula angle (°), which are indices of fluidity, and the angle of collapse (°) and angle of difference (°), which are indices of spoutability, were determined for the granules of Example 8 by the same method as described above. As a result, the angle of repose was 38°, the spatula angle was 49.8°, the angle of collapse was 34°, and the angle of difference was 4°.
[0119] <Example 9> 40 g of flavor (vanillin) was heated to 95° C. in a dry heat sterilizer to form a melt, and then rapidly cooled to 30° C. Meanwhile, 4 kg of sugar suspension E was prepared by the same method as in Example 5. 40 g of vanillin melt at 30° C. was mixed with sugar suspension E at 30° C. to obtain a mixed suspension (also referred to as mixed suspension I) (vanillin concentration in the solid content of mixed suspension I: 1.59% by mass).
[0120] The mixed suspension I was spray-dried using the above-mentioned spray dryer to obtain granules according to Example 9. At this time, the spray-drying conditions were all the same as those in Example 5.
[0121] [Appearance Observation] The granules according to Example 9 were subjected to external observation of the granule particles using a scanning electron microscope (SEM). The observation results (magnification: 1000 times) are shown in Fig. 9. As shown in Fig. 9, it can be seen that the granules according to Example 9 are formed by aggregation of crystalline sugar.
[0122] [Liquidity assessment] The fluidity of the granules of Example 9 was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity was evaluated as ◯.
[0123] Furthermore, the angle of repose (°) and spatula angle (°), which are indices of fluidity, and the angle of collapse (°) and angle of difference (°), which are indices of spoutability, were determined for the granules of Example 9 by the same method as described above. As a result, the angle of repose was 34°, the spatula angle was 44.3°, the angle of collapse was 26.5°, and the angle of difference was 7.5°.
[0124] [Sensory evaluation] The aroma of vanillin was strongly retained in the granules of Example 9. In order to evaluate the vanillin concentration in the granules, a sensory evaluation was carried out using the three-point discrimination method as described below.
[0125] First, the following solutions were prepared: (1) Blank: 1,240 mg of trehalose was completely dissolved in 1 L of warm water. (2) Granule solution: 1260 mg of the granules according to Example 9 was completely dissolved in 1 L of warm water (a dilution ratio that would result in a vanillin concentration of 0.02% if the aroma recovery rate were 100%). (3) Non-granular solution: 20 mg of vanillin and 1,240 mg of trehalose were completely dissolved in 1 L of warm water (dilution ratio resulting in a vanillin concentration of 0.02%).
[0126] 10 mL of each of the solutions (1) to (3) was serially diluted (maximum dilution: 256 times). 10 mL of each serial dilution was placed in a new Falcon tube, and the dilution was dropped onto the tip of a thick paper cut into a strip of filter paper (manufactured by Advantec Co., Ltd.), and two panelists evaluated the aroma and performed discrimination based on the three-point discrimination method. That is, it was confirmed whether the diluted solution of the granular solution or the diluted solution of the non-granular solution could be distinguished from two blanks. The results are shown in Table 13. In Table 13, the cases where the two panelists (panel 1 and panel 2) were able to distinguish the aroma of the diluted solution are indicated by ◯, and the cases where they could not be distinguished are indicated by ×. From the results shown in Table 13, it can be said that the granules of Example 9 sufficiently retain the aroma of vanillin even after spray drying.
[0127] [Table 13]
[0128] <Reference Example 1: Effect of temperature conditions during spray drying> The effect of temperature conditions in spray drying on the fluidity of granules was examined. Sugars (trehalose:sucrose 95:5) were added to warm water and dissolved while heating to 90°C in a hot water bath, to obtain a sugar solution with a Brix value of 61. This 90°C sugar solution was placed in a metal container and rapidly cooled to 30°C. While maintaining the temperature at around 30°C, the sugar solution was treated for 15 minutes at POWER MONITOR level 5 using an ultrasonic oscillator similar to that in Example 4, to obtain a sugar suspension.
[0129] The sugar suspension was spray-dried under the temperature conditions (inlet air temperature, outlet air temperature) shown in Table 14 below to obtain granules. The spray-drying conditions other than the temperature were the same as those in Example 5.
[0130] The flowability of each granule was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. The results are shown in Table 14.
[0131] [Table 14]
[0132] <Reference Example 2: Effect of sugar suspension concentration> We investigated the effect of the concentration (Brix value) of the sugar suspension on the fluidity of the granules. Sugars (trehalose:sucrose 95:5) were added to warm water and dissolved while heating to 90℃ in a water bath to prepare sugar solutions with Brix values of 50.0, 55.0, and 61.0. Each sugar solution was placed in a metal container and rapidly cooled to 30℃ to obtain a sugar suspension.
[0133] Each sugar suspension was spray-dried using the above-mentioned spray dryer to obtain granules. The spray-drying conditions were the same as those in Example 5.
[0134] The fluidity of each granule was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity of all granules obtained from sugar solutions with Brix values of 50.0, 55.0, and 61.0 was evaluated as ◯.
[0135] <Reference Example 3: Effect of atomizer rotation speed during spray drying> We investigated the effect of the atomizer rotation speed in spray drying on the fluidity of granules. Sugars (trehalose:sucrose = 95:5) were added to warm water and dissolved while heating to 90°C in a hot water bath, obtaining a sugar solution with a Brix value of 61. This 90°C sugar solution was placed in a metal container and rapidly cooled to 30°C to obtain a sugar suspension.
[0136] The sugar suspension was spray-dried at atomizer rotation speeds of 5000 rpm, 10000 rpm, and 18000 rpm to obtain granules. The spray-drying conditions other than the atomizer rotation speed were the same as those in Example 5.
[0137] The fluidity of each granule was evaluated by visual and manual inspection based on the above-mentioned evaluation criteria. As a result, the fluidity of all granules spray-dried at atomizer rotation speeds of 5000 rpm, 10000 rpm, and 18000 rpm was evaluated as ◯.
Claims
1. A granule containing at least one selected from the group consisting of crystalline sugar and crystalline sugar alcohol (excluding maltitol) and a functional material, The sugar and / or the sugar alcohol are partly in a crystalline state and partly in a non-crystalline state, The granules have an average particle size of the crystalline sugar and / or sugar alcohol of 1 to 80 μm.
2. The granule according to claim 1 , wherein the amorphous sugar and / or sugar alcohol and the functional material are retained in gaps formed between the crystalline sugar and / or sugar alcohol.
3. A granule according to claim 1 or 2, wherein the sugars and sugar alcohols are monosaccharides, disaccharides, trisaccharides and their sugar alcohols.
4. The granule according to any one of claims 1 to 3, wherein the functional material is an enzyme or a microorganism.
Citation Information
Patent Citations
Production of mixed powdery composition of ascorbic acid with maltitol having high fluidity
JP1997157285A
Solid spray dry powder and its production
JP1999114027A
Trehalose-containing composition
JP2000159788A
Functionally reinforcing composition for common food, health functional food or health supplemental food, and method for the same
JP2005034135A
Heat-resistant enzyme components
JP2010506564A